A novel combined technology for treating hypertrophic scars: adipose tissue extract combined with fractional CO2 laser - Cai, Yuan; Tian, Jiao; Li, Jianyi; Liu, Xing; Li, Fang; Zhang, Lanfang; Xiao, Shune; Jia, Changsha; Deng, Chengliang (Frontiers in Physiology, 2023)
Owing to the need for liposuction and its unsuitability for allogeneic transplantation, the clinical application of stromal vascular fraction gel (SVF-gel) combined with fractional CO2 laser for scar treatment is limited. Adipose tissue extract (ATE), rich in cytokines and growth factors, offers a more convenient option for clinical practice as it can be easily prepared using purely physical methods and has low immunogenicity. We aimed to evaluate the effectiveness of ATE combined with fractional CO2 laser in the treatment of hypertrophic scars.Methods: ATE was prepared using discarded liposuction fluid from patients undergoing liposuction. A rabbit ear hypertrophic scar model was established and treated with ATE, fractional CO2 laser, or a combination. PBS was used as a control. The scar appearance and histological changes were observed. The immunohistochemistry method was used to evaluate the expression of α-SMA, while perilipin was detected using immunofluorescence.Additionally, the level of adipogenic signal C/EBPα and PPARγ mRNA was studied.Results: Following treatment, the volume of hypertrophic scar decreased, resulting in a softer texture and thinner dermis. Additionally, there was a decrease in the infiltration of inflammatory cells, and the collagen arrangement became looser and more regular,and the expression of α-SMA also decreased, with the combination of ATE and fractional laser showing the most significant improvement. Moreover, the combination group was found to promote subcutaneous fat regeneration and increase the expression of adipogenic signals C/EBPα and PPARγ.The combination of ATE and fractional CO2 laser treatment has been shown to inhibit the development of hypertrophic scars. This effect may be attributed to the enhancement of adipogenesis and decrease in collagen deposition.